Bonding of acetylated wood. (2nd April 2016) - Bongers, F.; Meijerink, T.; Lütkemeier, B.; Lankveld, C.; Alexander, J.; Militz, H.; Lehringer, C.
Abstract : Through the modification of wood, various properties can be altered by chemical, physical or mechanical processes that influence the bonding quality and workability of gluing systems. This is evident for adhesion, pressing time, curing and glue line properties. Further, testing methods need to be evaluated on their applicability for determining the bonding quality of modified woods. In this paper, laboratory test results of non-load-bearing-laminated acetylated products are presented. The results are evaluated and discussed in respect to chemical composition, ultra-structure and other properties altered by the acetylation process.